БЎЛАЖАК ЎҚИТУВЧИЛАРНИ КАСБИЙ ТАЙЁРЛАШДА ТАЪЛИМ МЕТОДЛАРИДАН САМАРАЛИ ФОЙДАЛАНИШ ДИДАКТИКАНИНГ АСОСИЙ МУАММОЛАРИДАН БИРИ СИФАТИДА - Курбаниязова, З.К. (SCIENCE and SOCIETY, 2023)
The article reflects on educational methods, their description and types, and provides scientific considerations on how to guide future teachers to effective use of them in general high school life. In this, the issues of effective teaching of general pedagogy in higher pedagogic educational institutions, preparing the ground for teaching the teaching methodology of other professional disciplines, and taking into account the fact that pedagogy is a socio-humanitarian science, are given recommendations on teaching using traditional and modern teaching methods.